CFD analysis of first stage nozzle cooling optimization in power station gas turbine - Hasini H.; Fadhil S.S.A.; Jaafar M.N.M.; Malek N.A.; Ujir M.H. (Penerbit UTM Press, 2023)
Computational Fluid Dynamics analysis on First Stage Nozzle in full scale multi-stage power station gas turbine has been carried out. The main aim is to investigate the turbine thermal performance when cooling rate decreases at certain level. All calculations were executed using commercial CFD code, ANSYS FLUENT which is able to accurately predict the flow and conjugate heat transfer problem as demonstrated in this investigation. The modelling of gas turbine nozzle is assisted by geometric cloud data obtained from 3D scan. Preliminary calculation shows that at the given worst case scenario for, the maximum thermal stress experienced by the component is within the maximum yield strength of the nozzle material. However, the safety margin between the predicted stress and maximum allowable stress is very small. 2015 Penerbit UTM Press. All rights reserved.